If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -7)(x + -9) = (x + -3)(1 + -5x) Reorder the terms: (-7 + 6x)(x + -9) = (x + -3)(1 + -5x) Reorder the terms: (-7 + 6x)(-9 + x) = (x + -3)(1 + -5x) Multiply (-7 + 6x) * (-9 + x) (-7(-9 + x) + 6x * (-9 + x)) = (x + -3)(1 + -5x) ((-9 * -7 + x * -7) + 6x * (-9 + x)) = (x + -3)(1 + -5x) ((63 + -7x) + 6x * (-9 + x)) = (x + -3)(1 + -5x) (63 + -7x + (-9 * 6x + x * 6x)) = (x + -3)(1 + -5x) (63 + -7x + (-54x + 6x2)) = (x + -3)(1 + -5x) Combine like terms: -7x + -54x = -61x (63 + -61x + 6x2) = (x + -3)(1 + -5x) Reorder the terms: 63 + -61x + 6x2 = (-3 + x)(1 + -5x) Multiply (-3 + x) * (1 + -5x) 63 + -61x + 6x2 = (-3(1 + -5x) + x(1 + -5x)) 63 + -61x + 6x2 = ((1 * -3 + -5x * -3) + x(1 + -5x)) 63 + -61x + 6x2 = ((-3 + 15x) + x(1 + -5x)) 63 + -61x + 6x2 = (-3 + 15x + (1 * x + -5x * x)) 63 + -61x + 6x2 = (-3 + 15x + (1x + -5x2)) Combine like terms: 15x + 1x = 16x 63 + -61x + 6x2 = (-3 + 16x + -5x2) Solving 63 + -61x + 6x2 = -3 + 16x + -5x2 Solving for variable 'x'. Reorder the terms: 63 + 3 + -61x + -16x + 6x2 + 5x2 = -3 + 16x + -5x2 + 3 + -16x + 5x2 Combine like terms: 63 + 3 = 66 66 + -61x + -16x + 6x2 + 5x2 = -3 + 16x + -5x2 + 3 + -16x + 5x2 Combine like terms: -61x + -16x = -77x 66 + -77x + 6x2 + 5x2 = -3 + 16x + -5x2 + 3 + -16x + 5x2 Combine like terms: 6x2 + 5x2 = 11x2 66 + -77x + 11x2 = -3 + 16x + -5x2 + 3 + -16x + 5x2 Reorder the terms: 66 + -77x + 11x2 = -3 + 3 + 16x + -16x + -5x2 + 5x2 Combine like terms: -3 + 3 = 0 66 + -77x + 11x2 = 0 + 16x + -16x + -5x2 + 5x2 66 + -77x + 11x2 = 16x + -16x + -5x2 + 5x2 Combine like terms: 16x + -16x = 0 66 + -77x + 11x2 = 0 + -5x2 + 5x2 66 + -77x + 11x2 = -5x2 + 5x2 Combine like terms: -5x2 + 5x2 = 0 66 + -77x + 11x2 = 0 Factor out the Greatest Common Factor (GCF), '11'. 11(6 + -7x + x2) = 0 Factor a trinomial. 11((1 + -1x)(6 + -1x)) = 0 Ignore the factor 11.Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Solution
x = {1, 6}
| Siny=0.51 | | (3x+4)(x+1)=(x+1)(2x-1) | | 5m=58 | | 3a+-22=2a | | 9=-3m+12 | | -f(x)=(3x^2)-2x-3 | | (5x-4)(x-9)=(x+16)(1-5x) | | 3x+5y+3+3x-5y= | | x-5=2-12(x+6) | | x=40x | | 30+25x=20+55x | | 2a=37 | | x+0.1x=5000 | | -32=2+-7b | | Sin(x)=.88 | | Sinx=.88 | | 24c=1440 | | ((-7a^2b^3c^0)/(3a^2b^4c^3))^-4 | | (3x-4)(x-8)=(x-6)(4x-5) | | y^2-2y-4=16y-32 | | 5n-11=3n-13 | | 5x-3-30=4x-3+6x | | (-7a^2b^3c^0)/(3a^2b^4c^3)^-4 | | 27-2x=20-8x | | 32m=2496 | | -152=-8(6x+1) | | 5x+11=5x-17 | | 4y+(-2)=34 | | 22=-3(5k+6) | | 5x+11=-8x-17 | | 8x-27+146=180 | | Y=-x+250 |